Understanding the TeV Scale through LHC Data, Dark Matter and Other Experiments - Arkani-Hamed, Nima; Barbieri, Riccardo; De Curtis, Stefania; Heinemann, Beate; Reece, Matthew; Rolandi, Gigi; Wang, Lian-Tao (Il Colle di Galileo, 2014)
The workshop focused on new data from the LHC after the completion of its initial 7 TeV run, providing an opportunity to interpret the results and to plan for the future 14 TeV run. Particular attention was paid to the first serious indications for the discovery of a Higgs boson at a mass of 125 GeV. In addition to hearing from LHC experimentalists, attention was also given to input from experimenters at the Tevatron, as well as to the direct and indirect detection of dark matter, flavor physics, and other related searches. The main characteristic of the workshop was the close collaboration and intensive debate between theorists and experimentalists. The workshop also hosted a conference, jointly with the Johns Hopkins Series, on October 16/19, 2012.